Job promotion, staffing, and competence as drivers of employee performance: Evidence from Indonesia’s directorate general of national export development - Apriyanti, Herna Dwi (Journal of Economics and Business Letters, 2025)
This study examines how three human resource levers—job promotion, staffing/procurement, and employee competence—shape performance among civil servants at the Directorate General of National Export Development (DITJEN PEN), Ministry of Trade. Using an explanatory, cross-sectional survey of 154 employees (simple random sampling), we operationalized constructs on 5-point Likert scales and verified measurement quality via corrected item–total correlations and Cronbach’s alpha (all α ≥ 0.70 after two weak competence items were dropped). Correlational and regression analyses show that competence is the dominant predictor of performance (r = 0.676; β = 0.599, p < 0.001), job promotion has a positive but small effect (r = 0.181; β = 0.093, p = 0.025), and staffing/procurement perceptions are not statistically significant (r = 0.047; β = 0.016, p = 0.724). The full model is strong (F = 45.583, p < 0.001) with R² = 0.477, indicating that the three levers jointly explain nearly half of performance variance. Managerially, returns are highest from targeted competence development aligned to role demands, while promotion processes should be made more timely and transparently merit-based; staffing practices need re-engineering around person–job fit to reveal their contribution to performance. Limitations include cross-sectional design and perceptual measures; future work should integrate administrative data and test mediated pathways (e.g., staffing → competence → performance).